If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3X + -16 = 2X + 18 Reorder the terms: -16 + 3X = 2X + 18 Reorder the terms: -16 + 3X = 18 + 2X Solving -16 + 3X = 18 + 2X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2X' to each side of the equation. -16 + 3X + -2X = 18 + 2X + -2X Combine like terms: 3X + -2X = 1X -16 + 1X = 18 + 2X + -2X Combine like terms: 2X + -2X = 0 -16 + 1X = 18 + 0 -16 + 1X = 18 Add '16' to each side of the equation. -16 + 16 + 1X = 18 + 16 Combine like terms: -16 + 16 = 0 0 + 1X = 18 + 16 1X = 18 + 16 Combine like terms: 18 + 16 = 34 1X = 34 Divide each side by '1'. X = 34 Simplifying X = 34
| x^2+6x-8=3x-7 | | 4d-36-24d=2-16-4d | | 28=-4y+2(y+4) | | 6-2(x-2)=3(x+3)-9 | | 2d+15=27 | | x+5-3+3x-3x+x^2+4+x=35 | | 8c-c-1=9 | | 3(24-x)=6-x | | 14c-11=3(2c+7) | | 7=3-2+4x | | 6(w-2)+3w=24 | | (A+b)+3= | | 25xsquared-16=0 | | 3a+45+2a-10=180 | | .75n-2=-.875n+32 | | 3X-16=2N+18 | | 11x+10x=12x | | 5sinx+4cosx=0 | | 8c-(c-1)=9 | | -5x^2+39x+8=0 | | -24=3v+4(v+8) | | 4y+y+1=7y | | 3x-8+x+26=180 | | 6x-5(x-7)=-10 | | -24=3v+4(4+8) | | -5(r+7)=-87 | | 50+3x=x+82 | | -2=7(x-6)-2x | | 3x-7=5x-45 | | 9+8(5x+3)=-3-5(8x+3) | | -8x+9=-8x+5 | | -3.5x^2+42t+13=0 |